CHANGES OF IMMUNOREGULATORY PEPTIDES DURING SURGICAL TREATMENT OF GASTRIC CANCER - L. V. Matveeva (Медицинская иммунология, 2014)
A complex clinical study included twenty patients with gastric cancer (tumor stage II) before and after surgical treatment, and 30 healthy volunteers, under appropriate informed consent. In patients with gastric cancer, we have revealed some changes of immunoregulatory peptides in blood serum that showed correlations with histological types of the tumors. Maximal baseline (pre-surgery) levels of interleukins (IL- 1β, IL-2, IL-4, IL-10) were found in highly differentiated adenocarcinoma, whereas IL-17, interferon (IFNγ) were more expressed in low differentiated carcinoma. TNFα levels were independent on histological type of the tumor. Following surgical treatment, serum concentrations of IL-1β, IL-2, IL-10 were found to be increased, along with decrease in IL-4, IL-17, IFNγ, TNFα. Following surgical treatment of gastric cancer, no septic complications were observed in the patients during the follow-up period. Our results indicate to usefulness of cytokine profile data in patients with gastric cancer during their treatment, taking into account a histological type of the tumor, in order to predict clinical course following surgical treatment.